Keragaman Plankton dan Kondisi Perairan Tambak Intensif dan Tradisional di Probolinggo Jawa Timur - Utojo Utojo (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
This study aims to estimate the wealth and stability of traditional and intensive brackishwater pond waters through biological index calculation (diversity, uniformity and dominance of plankton) in traditional and intensive brackishwater pond waters of Probolinggo Regency, East Java Province. Sampling plankton and water from the site, considered to represent the diversity of plankton and water stability of traditional and intensive brackishwater pond. Plankton was collected using a plankton net no. 25, then preserved using 1% lugol solution. Measurement of water quality variables include temperature, salinity, dissolved oxygen and pH, whereas the laboratory analyzes that Total Organic Matter (TOM), NO2, NO3, NH3, PO4, Total Suspended Solids (TSS), and Fe. Plankton identification using microscope and calculation with cell counting method. The results of analysis of plankton in intensive brackishwater pond waters are obtained as much as 23 genera consisting of 16 genera of phytoplankton were included into three classes, namely Bacillariophyceae as much as 5 genera, Cyanophyceae 3 genera, Dinophyceae and Chlorophyceae, each of the four genera, whereas zooplankton consisting of 7 genera are included into two classes, namely Crustaceae 6 genera and Rotatoria 1 genus. In traditional brackishwater pond earned as much as 13 genera consisting of 8 genera of phytoplankton were included into Bacillariophyceae 5 genera, Cyanophyceae 2 genera, and Dinophyceae 3 genera, whereas zooplankton consisting of three genera are included into class Crustaceae 2 genera and Rotatoria 1 genus. Plankton abundance in intensive brackishwater pond ranges 702 - 4269 ind./L, diversity index of 0.26 -2.38, uniformity index of 0.10 - 1.5, and dominance index of 0.02 - 0.68. In traditional brackishwater pond have an abundance of plankton range 134 - 776 ind./L, diversity index of 0.10 - 1.97, uniformity index of 0.08 - 1.0, and dominance index of 0.01 - 0.75. Traditional and intensive brackishwater pond waters condition still within the limits that can be tolerated by the culture organism. Based on the index value of biological, diversity of genus in the intensive brackishwater pond is relatively higher than traditional brackishwater pond and the community stability moderate, whereas traditional brackishwater pond unstable. On average, the uniformity of the genus in both brackishwater ponds are relatively evenly and genus of plankton to dominate the others genus.